IMPROVING THE QUALITY OF SUGARCANE BAGASSE BY UREA AND CALCIUM HYDROXIDE ON GAS PRODUCTION, DEGRADABILITY AND RUMEN FERMENTATION CHARACTERISTICS - N. Gunun; P. Gunun; M. Wanapat; A. Cherdthong; S. Kang; S. Polyorach (Journal of Animal and Plant Sciences, 2017)
The objective of this study was to determine the influence of urea and whole soybean meal or calcium hydroxide [Ca(OH)2] treatment on sugarcane bagasse nutritive values and in vitro fermentation. The experimental design was a completely randomized design (CRD) and the dietary treatments were sugarcane bagasse treated with urea (0, 20, 40g/kg) and whole soybean meal or Ca(OH)2 (0, 25, 50g/kg). It was found that the protein content of sugarcane bagasse was significantly increased by whole soybean meal and urea treatment, and the values ranged from 65-71 g/kg DM. On the other hand, treatment of Ca(OH)2 50 g/kg with urea 40 g/kg could reduce (p<0.05) fiber content of sugarcane bagasse and the values were 533, 514 and 104 g/kg DM for NDF, ADF and ADL, respectively. Gas production from the insoluble fraction (b), potential extent of gas production (a+b) and cumulative gas production were significantly increased (p<0.05) in sugarcane bagasse treated with urea 40 g/kg and urea 40 g/kg + whole soybean meal 25 g/kg (55.3, 53.5 and 50.1 ml), respectively. Urea and Ca(OH)2 treatment could increase DM and OM degradability, true digestibility and microbial mass of sugarcane bagasse(p<0.05). Furthermore, the concentration of C3, C2 and C2:C3 were improved by urea and whole soybean meal or Ca(OH)2 treatment. In addition, methane production was decreased in sugarcane bagasse treated with urea 40 g/kg in the present study. Based on this experiment, it could be concluded that treatment of urea and Ca(OH)2 was an alternative method to improve the nutritive value of sugarcane bagasse, gas production, digestibility and ruminal fermentation characteristics.
Keywords: Sugarcane bagasse; Urea; Calcium hydroxide; Digestibility; Rumen fermentation